2014
DOI: 10.1021/ac403415m
|View full text |Cite
|
Sign up to set email alerts
|

Modification of Indium Tin Oxide with Dendrimer-Encapsulated Nanoparticles To Provide Enhanced Stable Electrochemiluminescence of Ru(bpy)32+/Tripropylamine While Preserving Optical Transparency of Indium Tin Oxide for Sensitive Electrochemiluminescence-Based Analyses

Abstract: Here, we report highly enhanced stable electrogenerated chemiluminescence (ECL) of Ru(bpy)3(2+) (bpy = 2,2'-bipyridyl) with tripropylamine (TPrA) coreactant on indium tin oxide (ITO) electrodes modified with amine-terminated dendrimers encapsulating catalytic nanoparticles while maintaining optical transparency of ITO and feasibility of the modified ITOs to sensitive ECL-based assays. As model systems, we prepared Pt and Au dendrimer-encapsulated nanoparticles (DENs) using amine-terminated sixth-generation pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
72
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 94 publications
(74 citation statements)
references
References 53 publications
2
72
0
Order By: Relevance
“…Bovine serum albumin (BSA), Ru(bpy) 3 3 , NaNO 3 , formamide, ascorbic acid, Na 2 HPO 4 , and NaH 2 PO 4 were supplied by Beijing Chemical Reagent Company (Beijing, China). Phosphate buffer solution (PBS, pH = 7.5, 0.1 M) was prepared using 0.1 M Na 2 HPO 4 and 0.1 M NaH 2 PO 4 .…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bovine serum albumin (BSA), Ru(bpy) 3 3 , NaNO 3 , formamide, ascorbic acid, Na 2 HPO 4 , and NaH 2 PO 4 were supplied by Beijing Chemical Reagent Company (Beijing, China). Phosphate buffer solution (PBS, pH = 7.5, 0.1 M) was prepared using 0.1 M Na 2 HPO 4 and 0.1 M NaH 2 PO 4 .…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
“…8 Alternately, considerable effort has been devoted to the development of the cathodic ECL of Ru(bpy) 3 2+ for avoiding the disadvantages of anodic reactions. 9−11 However, the cathodic ECL of Ru(bpy) 3 2+ is hardly happened in aqueous solutions owing to the high instability of reaction intermediates. 9 To solve these problems, scientists have aroused considerable interest in ECL resonance energy transfer (ERET) between suitable donors (e.g., luminol and quantum dots) and Ru(bpy) 3 2+ acceptors.…”
mentioning
confidence: 99%
“…Organic or metallic organic compound luminescent materials, such as luminol, tris(2,2'-bipyridyl)ruthenium(II) chloride, have been applied in the fabrication of electrochemiluminescence (ECL) immunosensors (Zhao et al 2015;Cao et al 2012;Kim, Y., Kim, J. 2014;Chen et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Electrochemiluminescence (ECL) has been attractive as a versatile electroanalytical technique for detection of a variety of analytes such as DNA, antibodies, proteins, and small molecules 16. This is because ECL provides beneficial features over photoluminescence, including low background, good spatial and temporal controllability, and simple instrumentation, mainly due to its unique luminescence‐generating process in which electrogenerated species undergo electron transfer reactions to form excited states emitting light near electrode surfaces 710. Specifically, luminol has been widely used in ECL‐based analyses since the ECL of luminol was first reported by Harvey 11, 12.…”
Section: Introductionmentioning
confidence: 99%
“…The other one is attachment of pre‐synthesized Au nanoparticles on electrodes with adhesive layers formed by silanization, self‐assembled monolayer (SAM) of thiolates, or layer‐by‐layer (LbL) assembly techniques 19, 24, 25. Recently, our group also reported electrochemical modification of electrode surfaces with amine‐terminated dendrimers encapsulating Au nanoparticles 26–29, which can be utilized for sensitive ECL‐based analyses 10. For example, we modified indium tin oxide (ITO) surfaces with dendrimer‐encapsulated Au nanoparticles (Au DENs) via electrooxidative grafting of amine terminals of the dendrimers onto ITO, and showed that the Au DEN‐modified ITO electrodes exhibited enhanced ECL emission of Ru(bpy) 3 2+ (bpy=2,2′‐bipyridyl) with tripropylamine (TPrA) co‐reactant even at lower applied potentials compared to bare ITOs 10, 29.…”
Section: Introductionmentioning
confidence: 99%